Correlation of psychosocial support concerns and depression in Deaf adults at Nairobi and Kajiado Counties, Kenya - Ngugi, Joyce, Wangari; Basnight-Brown, Dana; Arasa, Josephine (My University, 2021)
The Deaf are considered persons with disabilities owing to societal stigma resulting in inequality and discrimination. The sequential mixed methodology utilized a cross-sectional approach, with interviews translated and administered in Kenyan Sign Language. The MMSE screened for mental status, while PHQ-9 assessed for depression and WSAS for Psychosocial Support Concerns (PSS) concerns. Researcher-designed in-depth interviews explored qualitative themes. In addition, Focus Group Discussions, ethnographic observation checklist, and mental health providers’ key informant interviews corroborated data. Deaf adults (N=100, 83% response rate) reported inadequate counseling access (62%) while 55% reported no depression. However, 45% depicted clinically significant depression levels, with a notable 28% of Deaf adults also indicating suicidality. Content analyses revealed family, socioeconomic welfare and stigma as the topmost PSS concerns. The study found a significant positive correlation between depression and overall PSS concerns at 0.225 (p=0.024), and home management PSS concern with depression at 0.253 (p=0.011). ANOVA analyses revealed statistically significant differences between the depression categories’ effects on PSS concerns, F = 3.22, p =.026. T-tests analyses indicated that means for None and Mild Depression (M=8.93, SD=8.80) were significantly lower than for Severe depression, t (13) = -3.16, p = .007, 95% CI [-15.15, -2.85]; and Moderately Severe (M=12.64, SD=7.40) were significantly lower than for Severe depression, t (13) -2.67, p = .019, 95% CI [-9.57, -1.00]. The study implications are to design Deaf-friendly assessments. The study recommends Deaf-centric interventions and for further study, national census on Deaf mental health and development of instruments normed for Kenyan Deaf populations.
Keywords: psychological support; deaf adults; Nairobi; Kenya